(untitled) (Journal of Hama University, 2024)
A field experiment was conducted at the Agricultural Scientific Research Center in Al-Ghab (Syria) in order to study the effect of adding levels of nitrogen, phosphorus and potassium on some qualitative characteristics of Spunta potato tubers (protein, starch, dry matter). according to the split-sub split design (the main plots of nitrogen, one-time split and phosphorus treatments). split for two times the potassium treatments.) with three replications. Where nitrogen was added at levels of 0-80-160-240 kg N / ha in the form of urea (46% N), phosphorus at levels of 0-50-100-150 kg P2O5 / ha in the form of triple superphosphate (46% P2O5), and potassium at levels of 0 -50-100-150 kg K2O/ha in the form of potassium sulfate (50% K2O).The percentage of protein, starch, and dry matter was estimated, and the interaction between the levels of fertilizers used had a significant effect on increasing the percentages of each of protein, starch, and dry matter, compared to the control treatment.